Nutrient stress gradient in the bottom 5 cm of fast ice, McMurdo Sound, Antarctica - McMinn, A; Skerratt, J; Trull, T; Ashworth, CM; Lizotte, M (Polar Biology, 1999)
One-centimeter-scale vertical sampling of fast ice from McMurdo Sound, Antarctica reveals evidence of progressive nutrient limitation with distance above the ice/water interface. Over the bottom 6 cm photosynthetically active radiation increases by between 1.8 and 3 times, C:N increases from 6.8 to 19.8 and 13C increases from -18 to -12. Fatty acid corn position also changes with a consistent decline in polyunsaturated fatty acids and a rise in saturated fatty acids. These factors all suggest severe and progressive nutrient limitation with distance from the ice/water interface.